Normative Reasons Between Reasoning and Explanation - Logins, Artūrs (Humanities, 2022)
What are reasons to do something? This study assesses and critiques the current theories of normative reasons and provides a new theory of reasons as answers to normative why-questions, both for specialists and advanced students in epistemology, metaethics and ethics.This title is also available as Open Access on Cambridge Core.